(untitled) - Tsonis, Anastasios A. (Cambridge,New York, 2002)
An Introduction to Atmospheric Thermodynamics is a self-contained, concise but rigorous book introducing the reader to the basics of the subject. Introductory chapters provide basic definitions and some useful mathematical and physical notes. Following a treatment of the fundamental laws of classical thermodynamics, the book describes topics including the properties of moist air and atmospheric stability. Thermodynamic diagrams are used as tools in the forecasting of storm development. In the final chapter the author introduces the problem of weather prediction and the relevance of thermodynamics
Keywords: Atmospheric thermodynamics,Khí tượng học